EVALUASI KINERJA STRUKTUR GEDUNG DENAH L SDN 04 GAREGEH KOTA BUKITTINGGI DENGAN METODE ANALISIS NON LINIER - Sumpena, Harri; Bastian, Elfiani; Habirun, Asiya Nurhasanah (Ensiklopedia Research and Community Service Review, 2023)
Earthquake disaster is a destructive natural phenomenon. One of the concepts and analysis of earthquake resistant buildings is the concept of Performance Based Seismic Evaluation (PBSE) with the method of static push load analysis or pushover analysis. This method is able to provide information on the collapse pattern of existing buildings when subjected to earthquake forces that exceed the building's capacity, when direct collapse occurs, or when the building is able to behave non-linearly before total collapse occurs. The performance of the structure is evaluated by nonlinear analysis using SAP2000 software version 22, and the performance of the building against earthquakes and its collapse pattern can be clearly expressed in the form of a curve using Nonlinear Static Pushover Analysis. Nonlinear Static Pushover Analysis produces a capacity curve that describes the relationship between the base shear force and the displacement of the reference point on the roof.  The results of evaluating the structural performance of the SDN 04 Garegeh building in Bukittinggi City with the L plan, can be concluded based on nonlinear analysis or pushover analysis obtained ATC-40 displacement targets in the x-x direction of 0.02 and in the y-y direction of 0.02 shown in Table 5.5.4 ATC-40 (1996) the level of structural performance is a life safety condition, namely in the structure there is significant damage but has not yet collapsed, the major components of the structure will not collapse and the structure is not damaged.Keyword : Earthquake, Pushover Analysis, SAP2000, Curve Capasity, ATC-40